Improving Students' Interest In Learning Javanese Character By Using Augmented Reality - Halim, David Kristianto; Chandrawati, T. Brenda; Nugroho, Erdhi Wirdayanto (Soegijapranata Catholic University, 2024)
Javanese script is one of the materials taught in Javanese language lessons starting from elementary school to high school starting to be taught Javanese script. However, many students feel that this lesson is very boring and difficult for students because of the atmosphere when learning and teaching methods that only see from books and listen to lighting from teachers. Therefore, research was conducted by developing an Augmented Reality (AR) system, so that later it could add innovation in the method of teaching Javanese script in order to grow interest in students and students in learning[1]. The game created is called